Role of pentoxifylline in neonatal hypoxic ischaemic encephalopathy: a systematic review of animal studies - Florence Wong; Chandra Rath; Bhanu B. Gowda; Sanjay Patole (Laboratory Animal Research, 2024)
Abstract We systematically reviewed the evidence from animal studies assessing the effects of pentoxifylline on neonatal hypoxic-ischemic encephalopathy (HIE). The PubMed, EMBASE, EMCARE, MEDLINE, Cochrane Library, and Google Scholar databases were searched for randomized and quasi randomized controlled trials (RCTs) in December 2023 to determine the effects of pentoxifylline in animal models of HIE. The quality of the included studies was assessed via the SYRCLE risk of bias (ROB) tool. The certainty of evidence was assessed via the GRADE methodology. All seven included studies (n = 248) involved a rat HIE model in which pentoxifylline (25–150 mg/kg) was administered intraperitoneally. The majority had unclear ROB. All the studies reported a protective effect of pentoxifylline on HIE-induced organ injury. Mortality was comparable at pentoxifylline doses between 25 and 75 mg/kg but higher at 150 mg/kg than in the control group. Three studies reported macroscopic changes in HIE-affected organs. There was a significant reduction in cerebral infarction (40 and 75 mg/kg), hippocampal atrophy, and visible gut injury (60 mg/kg). A significantly lower number of Caspase 3 immunoreactive cells and necrotic cells were observed at the 60 mg/kg dose, whereas the 100 mg/kg dose had a deleterious effect. Three other studies reported significantly reduced levels of proinflammatory markers including IL-6 and TNF-alpha. Current evidence (with low uncertainty) from a rat model suggests that pentoxifylline has the potential to improve mortality and attenuate organ injury following HIE. Adequately powered, well-designed human RCTs are needed to confirm our findings.